2009
DOI: 10.3347/kjp.2009.47.3.205
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokine and Nitric Oxide Production by Human Macrophages Stimulated with Trichomonas vaginalis

Abstract: Trichomonas vaginalis commonly causes vaginitis and perhaps cervicitis in women and urethritis in men and women. Macrophages are important immune cells in response to T. vaginalis infection. In this study, we investigated whether human macrophages could be involved in inflammation induced by T. vaginalis. Human monocyte-derived macrophages (HMDM) were co-cultured with T. vaginalis. Live, opsonized-live trichomonads, and T. vaginalis lysates increased proinflammatory cytokines, such as TNF-alpha, IL-1beta, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
59
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 28 publications
2
59
1
Order By: Relevance
“…Park et al [14] showed that macrophage cytotoxicity against T. vaginalis is regulated by NO, with inhibition of trichomonicidal activity after macrophages exposure to L-NMMA. In other work, the parasites induced macrophage to produce proinflammatory cytokines, such as IL-1, IL-6, TNF-α, and NO, via NF-κB [37]. In vivo, it was observed the increase in polymorphonuclears (PMNs), vaginal epithelial cells, and reactive nitrogen intermediate (RNI) levels in mice infected with isolates from symptomatic patients as compared to asymptomatic subjects [38].…”
Section: Discussionmentioning
confidence: 86%
“…Park et al [14] showed that macrophage cytotoxicity against T. vaginalis is regulated by NO, with inhibition of trichomonicidal activity after macrophages exposure to L-NMMA. In other work, the parasites induced macrophage to produce proinflammatory cytokines, such as IL-1, IL-6, TNF-α, and NO, via NF-κB [37]. In vivo, it was observed the increase in polymorphonuclears (PMNs), vaginal epithelial cells, and reactive nitrogen intermediate (RNI) levels in mice infected with isolates from symptomatic patients as compared to asymptomatic subjects [38].…”
Section: Discussionmentioning
confidence: 86%
“…Extensive reports have shown that common protozoan pathogens, such as T. cruzi, E. histolytica, T. vaginalis, and Leishmania, cause upregulation of proinflammatory cytokines to induce immune responses (46)(47)(48)(49). Macrophages, the first cells that encounter pathogens that cross the intestinal epithelium, may be resident in strategic locations, such as the lamina propria, or may be recruited to the inflamed gut by chemokine signals (38,50).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TvSP induce intracellular reactive oxygen species (ROS) generation and apoptosis of human neutrophils (13,14). Infection with T. vaginalis is clinically important and linked to an increased incidence of human immunodeficiency virus type 1 transmission, preterm delivery, low birth weight, and cervical cancer (11)(12)(13). However, the signaling mechanism of TvSP-induced inflammatory responses at the mucosal tissues infected with T. vaginalis is not fully understood.…”
mentioning
confidence: 99%
“…It is evident that TvSP directly stimulate various immune cells to perform various functions. For example, TvSP stimulate human neutrophils to produce the proinflammatory cytokines and chemokine, leading to the recruitment of various inflammatory cells (11,12). In addition, TvSP induce intracellular reactive oxygen species (ROS) generation and apoptosis of human neutrophils (13,14).…”
mentioning
confidence: 99%